Industrial anthropogenic paradynamic and paragenetic landscape systems of Vinnytsya - Яцентюк, Ю. В. (Man and Environment. Issues of Neoecology, 1970)
The structure of industrial anthropogenic paragenetic and paradynamic landscape systems of Vinnitsa are considered. In subzone direct air and indirect impact of industrial minerall and scapes stands on 3 types of anthropogenic and paragenetic aradinamic landscape zones: permissible, moderate and dangerous levels of pollution.Ranges of individual paragenetic and paradynamic fields of all the zones of influence of interconnected water and air currents. Within Vinnitsa allocated 11 paragenetic and anthropogenic landscape paradynamic fields with anacceptable level of environmental pollution,18 fields with a moderate level of contamination and 5 fields with dangerous levels of pollution. At the outbreak of dangerous levels of pollution fields increases the overall incidence of children and adults on chronic respiratory diseases and impaired functional state of the cardiovascular system.